THE IMPORTATNT LOGISTICAL CENTERS AND PARKS IN THE BRATISLAVA REGION - Kubasakova, Iveta (Doprava a spoje, 2011)
This article was written about ten logistics centers and logistics parks, which are operating in Bratislava area. It is written about possibilities, where the companies could storage their components and goods. In the article are some information, which can using some companies as cold - freezer storage and ADR transportation or storage.